Divergence of Legionella Effectors Reversing Conventional and Unconventional Ubiquitination - Kitao, Tomoe; Nagai, Hiroki; Kubori, Tomoko (Frontiers in Cellular and Infection Microbiology, 2020)
The intracellular bacterial pathogen Legionella pneumophila employs bacteria-derived effector proteins in a variety of functions to exploit host cellular systems. The ubiquitination machinery constitutes a crucial eukaryotic system for the regulation of numerous cellular processes, and is a representative target for effector-mediated bacterial manipulation. L. pneumophila transports over 300 effector proteins into host cells through its Dot/Icm type IV secretion system. Among these, several effector proteins have been found to function as ubiquitin ligases, including unprecedented enzymes that catalyze ubiquitination through unconventional mechanisms. Recent studies have identified many L. pneumophila effector proteins that can interfere with ubiquitination. These effectors include proteins that are distantly related to the ovarian tumor protein superfamily described as deubiquitinases (DUBs), which regulate important signaling cascades in human cells. Intriguingly, L. pneumophila DUBs are not limited to enzymes that exhibit canonical DUB activity. Some L. pneumophila DUBs can catalyze the cleavage of the unconventional linkage between ubiquitin and substrates. Furthermore, novel mechanisms have been found that adversely affect the function of specific ubiquitin ligases; for instance, effector-mediated posttranslational modifications of ubiquitin ligases result in the inhibition of their activity. In the context of L. pneumophila infection, the existence of enzymes that reverse ubiquitination primarily relates to a fine tuning of biogenesis and remodeling of the Legionella-containing vacuole as a replicative niche. The complexity of the effector arrays reflects sophisticated strategies that bacteria have adopted to adapt their host environment and enable their survival in host cells. This review summarizes the current state of knowledge on the divergent mechanisms of the L. pneumophila effectors that can reverse ubiquitination, which is mediated by other effectors as well as the host ubiquitin machinery.